Students’ Self-regulation in English Reading Comprehension during Online Class in Yogyakarta Private Senior High School - Klara Tyas Sulistyawati; Paulus Kuswandono (Journal of English Teaching, 2022)
The learning process in Indonesia has predominantly been conducted online since March 2020 due to the COVID-19 pandemic. This online learning mode has also influenced students’ motivation in learning, especially in comprehending reading texts. Considering that problem, the researchers sought to investigate how the students regulated their comprehension in reading during an online class. This research used a mixed-method. The questionnaires were distributed to 30 students and analyzed as quantitative data. Then, the researchers chose four students randomly for interview purposes. The interview transcript was used as qualitative data. In conclusion, not all of the students could regulate themselves in comprehending English text during the online class well. Based on the data, students who could regulate themselves in comprehending the English texts during online class should develop the following procedure: (1) implementing learning autonomy, (2) implementing learning focus, and (3) using critical thinking. Meanwhile, students who could not regulate themselves well were inclined to perform minimally. Since students had different ways to regulate themselves, the teacher needed to monitor the students in online learning process so that the students could achieve a meaningful learning process. To improve students’ regulation in reading comprehension, the teacher can implement suitable learning activities.